SECURING DEMOCRACY IN CYBERSPACE: VOTER DATA LEAKS IN INDONESIA'S 2024 ELECTION - Pradnyana, I Putu Hadi; Utama, Rhesa Anggara; Sasmita, Ni Wayan Ditha (Universitas Riau Kepulauan, 2024)
This research examines the impact of voter data leaks on the essence of democracy, focusing on participation, accountability, and transparency. Using a descriptive qualitative method and secondary data sources, this research analyzes voter data breach incidents in Indonesia’s 2024 general election as case studies. The findings reveal that voter data breaches threaten public participation by reducing voters' sense of security and trust. Additionally, government accountability is undermined due to the failure to protect citizens' personal data, diminishing legitimacy and public trust. The transparency of the electoral process is also negatively affected, hindering the necessary verification and validation for fair and trustworthy election outcomes. The study concludes that proactive measures from the government are essential to enhance cybersecurity, including the development of stringent regulations, investment in advanced security technologies, and increased public awareness. These steps are crucial to protecting voter data, maintaining the integrity of democracy, and ensuring that every vote is counted honestly and transparently. Therefore, the security of voter data is key to preserving public trust and the essence of democracy in the digital age.